Japan : Basel Core Principles for Effective Banking Supervision: Detailed Assessment of Compliance. (IMF Staff Country Reports; Country Report, 2012)
This report focuses on the effectiveness of the Japanese Financial Supervisory Authority (FSA) and the Bank of Japan in supervising and regulating the Japanese financial system during the March 2011 earthquake. The report also highlights Japan's compliance with the Basel Core Principles (BCPs) for Effective Banking Supervision. Japan has introduced various improvement measures to its regulatory framework and has an operational set-up that largely complies with the norms of the BCP's. In general, the mandates for supervision are structured and FSA given a free hand on supervisory responsibilities.